The Role of Strategic Flexibility on Business Survival - Harisatul Agustin; Syarifa Hanoum; Tasya Arihul Wardah (Institut Teknologi Sepuluh Nopember, 2023)
The COVID-19 pandemic has had severe consequences across various aspects of life, significantly impacting the culinary sector, which is a crucial part of the tourism industry. Restrictions on dine-in services compelled businesses to adapt to take-out options, resulting in significant repercussions. To navigate these challenging times and ensure the survival and growth of the culinary industry, entrepreneurs and restaurant managers had to adopt innovative strategies. Income reductions affected nearly 43% of culinary businesses during this period. To investigate the dynamics further, the research conducted a PLS-SEM analysis, surveying 163 MSME owners or restaurant managers operating in the Surabaya city region, who had received government support and continued their business operations amidst the pandemic. The analysis revealed that strategic flexibility played a pivotal role in influencing marketing innovation and process innovation. However, the impact of marketing innovation on business survival was not direct, while process innovation significantly influenced business survival. Interestingly, the study observed that government support did not alter the relationships between marketing innovation, process innovation, and business survival.